Projection-defined hypothalamic outputs differentially regulate thermogenesis and lipolysis - Hyeonyoung Min; Qi Zheng; Yunlei Yang (Proceedings of the National Academy of Sciences, 2026)
The ventromedial hypothalamus (VMH) is a key regulator of energy homeostasis, linking central neural activity to peripheral metabolic function. Within the VMH, neurons expressing steroidogenic factor-1 (SF-1; VMH SF1 ) are essential for regulating energy expenditure, yet the projection-defined pathways through which they differentially control distinct adipose depots remains unclear. Here, we use projection-specific optogenetic and chemogenetic manipulations in SF1-Cre mice to identify two anatomically and functionally distinct VMH SF1 output pathways with complementary metabolic roles. Activation of the VMH SF1 →rostral periaqueductal gray (rPAG) projection selectively stimulates thermogenesis in brown adipose tissue, elevating its temperature and thermogenic gene expression, whereas activation of the VMH SF1 →paraventricular thalamus (PVT) pathway promotes lipolysis in white adipose tissue without engaging thermogenic programs. Both effects require intact innervation and target-region activity. These findings reveal that VMH SF1 neurons direct distinct hypothalamic output pathways to differentially regulate thermogenesis and lipid mobilization, delineating a modular neural framework for flexible, state-dependent coordination of energy expenditure and substrate utilization.